School Security and Safety Challenges in Nigeria: Evaluating the Existential Threats of Domestic Terrorism in the North East Region - Awajiowa Nte (Program Studi Pendidikan Sejarah - Universitas Samudra, 2023)
Abstract The ubiquity of terrorism cannot be overemphasized as it has become a global common phenomenon. Schools are easy prey of terrorist attack since they lack the maximum security apparatuses that other state institutions possess. All over the world, terrorist attacks have taken place inside and beside school premises raising serious concern for government, security experts and school authorities. The recurring events of school shootings that keep taking place in the United States of America, Beslan Russia and even in Norway have proven that no school is totally immune from attacks by insiders, criminals, terrorists and non-state actors. Consequently, schools should be protected from these threats given the public emotion, sensitivity and global concerns about places of learning. In the last decade or so, Nigeria has gone through the harrowing experiences of terrorist attacks on schools especially in the Northern part of the country and the North East in particular by Boko Haram, ISWAP and currently armed bandits. This study therefore examines this ugly menace that has defied sustainable solutions to insecurity and safety threats in Schools. The study is descriptive in nature and gathered information from materials already available and questionnaires from individuals and schools authorities.